Wealth inequality, unequal opportunities and inefficient credit market - Giuseppe Coco; Giuseppe Pignataro (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
This paper investigates the impact of heterogeneous wealth on credit allocation from an egalitarian opportunity and an efficiency point of view. Under asymmetric information on both wealth and the responsibility variable there is no trade-off between equality and efficiency, actually wealth inequality delivers both inequality of opportunity and inefficiency. Due to decreasing absolute risk aversion, poor entrepreneurs, other things equal, realize better projects. This notwithstanding, due to the bidimensional hidden information, they may be rationed out or obtain a loan only at the cost of cross subsidizing bad projects realized by rich entrepreneurs. In the first case inefficiency arises in the form of insufficient investment, in the second in the form of inefficient projects being realized. An egalitarian redistribution of endowments may lead to perfect screening, no inefficiencies in the allocation of credit and equality of opportunity.
Keywords: D31; D82; G21; 330